In vitro cell model to dilucidate the underlying molecular mechanism associated with ophthalmic manifestation of congenital disorders of glycosylation: studying an ALG2-CDG patient - Cubilla, Marisa Angelica (2025)
Introduction: Congenital Disorders of Glycosylation (CDG) are severe disruptions in the synthesis of glycoconjugates, resulting in inherited metabolic conditions. These multisystem diseases, typically inherited in an autosomal recessive manner, have an occurrence rate of approximately 1 in 20,000 to 1 in 50,000 live births. The clinical presentation of CDG is highly varied and complex, with neurological symptoms being predominant, affecting multiple organ systems. The process of glycosylation, a critical post-translational modification, is tightly controlled by proteins encoded by over 250 genes, and mutations in any of these genes are known to cause CDG. The discovery of new associated genes over recent years has accelerated; comprehensively characterizing these, especially rare ones, will aid in identifying novel therapeutic targets, improving prognostic evaluations, and developing effective treatments. In vitro models (such as cell lines or patient-derived “clinical-grade” cells) are essential for advancing CDG research. Notably, 60% of defects affecting N- or O-glycosylation impact the eyes, leading to photoreceptor degeneration and cell death. The 661W cell line, derived from immortalized mouse retinal cells and expressing specific ocular markers, serves as a valuable experimental model to study the ocular involvement in CDG.Methods: In this study, we utilized the 661W cell line to explore the molecular consequences of a homozygous variant in the ALG2 gene (c.752G>T; p.Arg251Leu), which encodes the enzyme α-1,3-mannosyltransferase. Following transfection with a plasmid carrying the variants of the gene of interest ALG2 p.Arg251/p.Arg251, we carefully evaluated changes in gene expression using RT-PCR and Western blotting.Results: Our results suggest that the 661W cell line may serve as a useful model for examining the potential impact of a specific mutation, supporting a possible link between the mutation’s molecular effects and clinical disease progression.Discussion: These findings could provide valuable insights to inform the development of targeted therapeutic strategies within the framework of personalized medicine.